REVIEW: PERBAIKAN PROFIL LIPID DENGAN PEMILIHAN OLAHRAGA YANG TEPAT BERDASARKAN KONDISI INDIVIDU - Tiara Anisya Rachman; Sri Agung Fitri Kusuma; Ramdan Pelana (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Diseases related to lipid metabolism continue to be a worldwide concern. Abnormal levels of lipids, especially Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL) can cause cardiovascular diseases such as heart attacks and strokes. Until now, these two diseases are the main causes of death globally according to the World Health Organization (WHO). In addition to pharmacological therapy such as statins, lipid levels can also be lowered through exercise. Therefore, this review article aims to provide information about the types of exercise that can reduce blood lipid levels according to the conditions of individual groups in terms of age, gender, and other special groups based on certain disease conditions. It was found that the most widely practiced exercise in all individual groups was aerobic exercise. This exercise is suitable for pregnant and postmenopausal women. Concurrent training is also appropriate for postmenopausal women. Whereas in premenopausal women, water exercise is more effective than concurrent training. In adult men, an effective exercise to do is the nordic walk. In the elderly, exercise that can be done is stationary cycling with one leg at high intensity. Patients with special conditions with Autistic Spectrum Disorder (ASD) can perform coordination and strength exercises. As for Multiple Sclerosis (MS) patients, the exercises that can be done are walking/running and high-intensity resistance training. The application of the type of exercise according to individual conditions can effectively prevent the increase in lipid levels.